LEADERS’ ROLE IN INFECTION PREVENTION AND CONTROL FIGHTING THE INVISIBLE AND INVINCIBLE... IF ONLY... - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2004)
If only we could enlarge the microbes to a sharp, clearly visible image and give it character, perhaps then we could terrorize people into a new respect for infection prevention, control, and practice compliance. It would remind us there is no safe place to run and hide – they are inside you, all over you and on everything you touch! Microbes falling over each other to get to you and to everyone around you. Scary thought!